Proton Pump Inhibitor-Induced Galactorrhea in a Kidney Transplant Recipient: A Friend or Foe? - Marios Prikis; Julie MacDougall; Nina Narasimhadevara (Case Reports in Transplantation)
Over the last decades, proton pump inhibitors (PPIs) have been widely used as the mainstay for treatment and prevention of gastrointestinal side effects, gastroesophageal reflux, and peptic ulcer disease. However, their safety profile has come into question recently after reports relating them to several side effects as well as kidney disease. Omeprazole, one of the mainly used PPIs, is almost entirely metabolized by the liver but the resulting metabolites are renally excreted. These metabolites may inhibit cytochrome P450 2C19 (CYP2C19) and cytochrome P450 3A4 (CYP3A4) reversibly, but as recent evidence suggests, they may also be involved in causing kidney disease. In the setting of renal dysfunction, these metabolites will not be excreted from the body and will accumulate further causing kidney damage and inhibiting CYP enzymes to a greater extent. Abnormally high serum prolactin levels leading to galactorrhea may be the result of such an accumulation. To our knowledge, there have been only three previously reported cases of PPI-induced galactorrhea in the literature but none in a kidney transplant recipient. In patients with established kidney disease and reduced glomerular filtration rate like kidney transplant recipients, the use of PPIs should be thoroughly assessed. Reduced clearance of their metabolites may lead to progression of the kidney disease and lead to more unwanted side effects. We present a case of a female kidney transplant recipient with worsening allograft function who presented with sudden galactorrhea and hyperprolactinemia while on a high-dose omeprazole for gastroesophageal reflux disease.